ANALISIS KEPUTUSAN PEMBELIAN PADA PT. INTERNATIONAL HARDWARE INDO KOTA BATAM DAN PT. MULIATAMA BATAM - Hendri Kremer; M. Arpah; Mohamad Aras; Hazriyanto Hazriyanto; Daris Purba (JURNAL CAFETARIA, 2023)
In this study, it was examined about sales decisions in two companies engaged in the same field, namely as distributors of goods. The two companies are PT International Hardware Indo and PT Muliatama Batam. These two companies both operate in Batam but the level of purchasing decisions of each company needs to be calculated quantitatively. This study used a different test approach using an independent sample t-test. Purchasing decision data was obtained from the entire population sampled using the saturated sample technique. Data retrieved in June-July 2021. Before hypothesis testing, the data is tested for quality by tests of normality and homogeneity. The results of data quality testing show that distributed data is normal and homogeneous. The results of the hypothesis test showed that there was a significant difference between the purchasing decision at PT International Hardware Indo and PT Muliatama Batam. This study concluded that PT Muliatama Batam is better quantitatively in terms of purchasing decisions than PT Muliatama Batam.